Effects of extreme drought on specific leaf area of grassland species: A meta‐analysis of experimental studies in temperate and sub‐Mediterranean systems. (29th March 2017) - Wellstein, Camilla; Poschlod, Peter; Gohlke, Andreas; Chelli, Stefano; Campetella, Giandiego; Rosbakh, Sergey; Canullo, Roberto; Kreyling, Jürgen; Jentsch, Anke; Beierkuhnlein, Carl
Abstract: Here, we conducted a meta‐analysis of experimental drought manipulation studies using rainout shelters in five sites of natural grassland ecosystems of Europe. The single studies assess the effects of extreme drought on the intraspecific variation of the specific leaf area (SLA), a proxy of plant growth. We evaluate and compare the effect size of the SLA response for the functional groups of forbs and grasses in temperate and sub‐Mediterranean systems. We hypothesized that the functional groups of grasses and forbs from temperate grassland systems have different strategies in short‐term drought response, measured as adjustment of SLA, with SLA‐reduction in grasses and SLA‐maintenance in forbs. Second, we hypothesized that grasses and forbs from sub‐Mediterranean systems do not differ in their drought response as both groups maintain their SLA. We found a significant decrease of SLA in grasses of the temperate systems in response to drought while SLA of forbs showed no significant response. Lower SLA is associated with enhanced water‐use efficiency under water stress and thus can be seen as a strategy of phenotypic adjustment. By contrast, in the sub‐Mediterranean systems, grasses significantly increased their SLA in the drought treatment. This result points towards a better growth performance of these grasses, which is most likely related to their strategy to allocate resources to belowground parts. The observed SLA reduction of forbs is most likely a direct drought response given that competitive effect of grasses is unlikely due to the scanty vegetation cover. We point out that phenotypic adjustment is an important driver of short‐term functional plant response to climatic extremes such as drought. Differential reactions of functional groups have to be interpreted against the background of the group's evolutionary configuration that can differ between climatic zones. Abstract : We conducted a meta‐analysis on the effects of extreme drought on the intraspecific variation of the specific leaf area (SLA, a proxy of plant growth) using experimental drought‐manipulation studies in five sites of natural grassland ecosystems of Europe. We found a significant decrease of SLA in grasses of the temperate systems in response to drought, while SLA of forbs showed no significant response. By contrast, in the sub‐Mediterranean systems, grasses significantly increased and forbs decreased their SLA in the drought treatment. We provide mechanistic explanations for the obtained findings and conclude that differential reactions of functional groups have to be interpreted against the background of the group's evolutionary configuration that can differ between climatic zones.